OPTIMIZATION OF SUNGAI PENUH CITY GOVERNMENT ASSET DATABASE USING GEOGRAPHIC INFORMATION SYSTEM (GIS) - ASTUTI, RINNA; Zulherman; Utama, Wahyudi P. (Jurnal Infrastruktur, 2024)
One of the strategic issues facing the City of Sungai Penuh is flooding, as indicated by the Detailed Spatial Planning (Rencana Detail Tata Ruang or RDTR) for the years 2021–2024. Despite efforts to manage the drainage, there is currently no digital-based drainage asset database in the City of Sungai Penuh. The aim of this study is to optimize the asset database used by the Geographic Information System (GIS) at the Public Works and Housing Agency (Dinas PUPR) of Sungai Penuh. The objective is to enhance the efficiency of asset management owned by the Dinas PUPR of Sungai Penuh in terms of utilization, management, and maintenance. This research employs the waterfall method for system design and part analysis to evaluate the condition of the asset database. According to this study, the drainage infrastructure asset database system still does not meet user needs from various perspectives. Several aspects require improvement. The development of a drainage infrastructure asset database through the implementation of a Geographic Information System (GIS), aligned with findings from questionnaires and analysis using the PIECES framework, has proven to meet user expectations. This is particularly evident in the aspects of delivering relevant information, data security, and the availability of adequate services. This evaluation can be substantiated through the average Satisfaction Response (RK) score, which indicates user satisfaction levels ranging from satisfied to very satisfied.